Candi Prambanan: Pengelolaan Dan Potensi Persoalannya - Sugeng Riyanto (Balai Arkeologi Yogyakarta, 2007)
In modern archaeological theory, various views have emerged as to how archaeologists do not only know the past, but it is time to present the past in the present along with various meanings so that it is also useful for the present. For this reason, various frameworks and theories regarding Public Archeology, CRM frameworks,